A STUDY ON RECENT NEW RESULTS ON SOME GRAPH VALUED FUNCTIONS - Shetty, Jayashree. B; Muddebihal, M. H (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In this paper, the result on some valued function(digraph operator), namely the block line cut vertex digraph BLC(D) of a digraph D is defined, and the problem of reconstructing a digraph from its block line cut vertex digraph is presented. Outer planarity, maximal outer planarity, and minimally non-outer planarity properties of these digraphs are discussed.